The diagnostic value of a change in bowel habit for colorectal cancer within different age groups. Issue 2 (1st March 2020) - McCulloch, Sofia M; Aziz, Imran; Polster, Annikka V; Pischel, Andreas‐Bernd; Stålsmeden, Henrik; Shafazand, Morteza; Block, Mattias; Byröd, Gunnar; Lindkvist, Björn; Törnblom, Hans; Jonefjäll, Börje; Simren, Magnus
Abstract : Background: Change in bowel habit as a sole alarm symptom for colorectal cancer is disputed. Objective: We investigated the diagnostic value of change in bowel habit for colorectal cancer, particularly as a single symptom and within different age groups. Methods: This retrospective cohort study examined colorectal cancer fast track referrals and outcomes across four Swedish hospitals (April 2016–May 2017). Entry criteria constituted one or more of three alarm features: anaemia, visible rectal bleeding, or change in bowel habit for more than 4 weeks in patients over 40 years of age. Patients were grouped as having only change in bowel habit, change in bowel habit plus anaemia/bleeding or anaemia/bleeding only. Results: Of 628 patients, 22% were diagnosed with colorectal cancer. There were no cases of colorectal cancer in the only change in bowel habit group under 55 years, while this was 6% for 55–64 years, 8% for 65–74 years and 14% for 75 years and older. Among subjects under 55 years, 2% with anaemia/bleeding had colorectal cancer, this increased to 34% for 55 years and older ( P  < 0.0001). Change in bowel habit plus anaemia/bleeding gave a colorectal cancer prevalence of 16% in under 55 years and increased to 30% for 55 years and older ( P  = 0.07). Conclusion: Change in bowel habit as the only alarm feature has a low diagnostic yield for colorectal cancer in patients under 55 years.